Theological Analysis of the Religious Terms in the Chingiz Aitmatov’s Novel “The Day Lasts More Than a Hundred Years” - Ажимаматов, Зайлабидин (Scientific Journal of Faculty of Theology, 2018)
In the work ‘The Day Lasts More Than a Hundred Years’ Chingiz Aitmatov addresses a group of religious terms. For example, you can meet such religious terminology as God, heaven and hell, end of the world, the Koran. In this work, the great writer puts more emphasis on the Islamic faith, ritual practice. Therefore, the book ‘The Day Lasts More Than a Hundred Years’ contains spiritual and religious values, inherent in Kyrgyz nation.